2022
DOI: 10.3390/ijerph19073957
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown in Patients with Chronic Diseases: A Cross-Sectional Study

Abstract: Background: We aimed to investigate the impact of the first COVID-19 lockdown on medication adherence, physician access, lifestyle behaviours, and mental health in patients with chronic conditions. Methods: A cross-sectional phone survey was conducted in 1274 housebound adults recruited from 8 regional chronic disease cohorts (CLEO CD study: NCT04390126). Results: Medication adherence was 97%; 305 (41%) patients declared that at least one scheduled visit with a physician was missed during the first lockdown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The prevalence of patients who reported a change in their medication intake during the COVID-19 pandemic is significantly lower in our study when compared with studies conducted among long-term patients in the US [29,30] but similar to other studies conducted in Europe [31][32][33][34][35][36]. Older and highly educated individuals were less likely to see their medication intake impacted by the pandemic, which is consistent with other studies [29,37], while taking medication for the respiratory system increased, by over three times, both the odds of having more regular medication intake and of increasing the medication dosage.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of patients who reported a change in their medication intake during the COVID-19 pandemic is significantly lower in our study when compared with studies conducted among long-term patients in the US [29,30] but similar to other studies conducted in Europe [31][32][33][34][35][36]. Older and highly educated individuals were less likely to see their medication intake impacted by the pandemic, which is consistent with other studies [29,37], while taking medication for the respiratory system increased, by over three times, both the odds of having more regular medication intake and of increasing the medication dosage.…”
Section: Discussionsupporting
confidence: 86%
“…The literature describes several reasons for modifying or discontinuing treatment, including fear of being infected by attending hospitals or doctor appointments, a lack of access to medications and a perceived risk of severe COVID-19 symptoms due to the immunosuppressive effect of some medications [4,40]. In addition, our results show that more than 30% of medication discontinuations or adjustments were conducted without discussion with a healthcare professional, which is higher than reported in two other studies [29,31]; the literature in this area is lacking and needs further attention.…”
Section: Discussionmentioning
confidence: 54%
“…In a recent COVID-19 study in France, increased screen time was the most prevalent unhealthy behavior observed, and urban-dwelling participants were nearly twice as likely to report increased unhealthy behaviors (such as screen time, but also increased alcohol intake, smoking, lower sleep quality, etc.) compared to rural participants [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies were observational studies, being 45 (91.8%) crosssectional studies and 4 (8.2%) longitudinal studies (Table 1). Studies were done in Argentina (26), Australia (27)(28)(29), Chile (30), China (31,32), Cuba (32), Egypt (33), Kuwait (33), France (34), Iran (35)(36)(37)(38)(39)(40), Italy (41)(42)(43)(44)(45)(46)(47)(48), Montenegro (49), Poland (50, 51), Portugal (52), Serbia (53,54), Spain (31,32,55), Turkey (56)(57)(58), and the United States of America (47,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Most of the articles demonstrated to have reasonable methodological quality.…”
Section: Resultsmentioning
confidence: 99%